Implementation of Conversational Marketing as a Strategy to Improve Business Performance for Micro, Small and Medium Enterprises (MSMEs) - Khalik, Idham; Perdana Siregar, Ade; Malinda SB, Istiqomah (Dinasti International Journal of Digital Business Management, 2025)
Corresponding Author: The fact that fewer micro, small, and medium-sized enterprises (MSMEs) are operating in Jambi Province suggests that their subpar performance is causing them to fail and have a negative effect on the province's GDP.  In order to fulfill their goals of sustaining and growing their firm, business organizations employ marketing tactics.  Unlike big corporations, micro, small, and medium-sized enterprises (MSME) pitch their products and services around the idea of entrepreneurship.One approach to implementing marketing for MSMEs is entrepreneurial marketing. Utilizing technology for online transactions, implementing a community-focused strategy is very important because the key to the success of this strategy is interaction. Conversational marketing is an innovative approach to understanding and meeting consumer requirements through two-way communication with consumers. Because technology is advancing at such a quick pace, MSMEs need to employ innovative marketing methods that are based on technology.  By examining the effect of entrepreneurial marketing on business success via conversational marketing mediation, this study addresses a significant knowledge vacuum. The objectives of this research are (1) the influence of entrepreneurial marketing on business performance in MSMEs; (2) examine the influence of conversational marketing on business performance in MSMEs; (3) examine the influence of entrepreneurial marketing on conversational marketing in MSMEs; (4) examine the role of conversational marketing in mediating the influence of entrepreneurial marketing on business performance in MSMEs. This research uses quantitative research methods which are carried out by forming and testing models. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software